Minimally Invasive Versus Sternotomy for Mitral Surgery in the Elderly: A Systematic Review and Meta-Analysis. Issue 4 (July 2021) - Hage, Ali; Hage, Fadi; Al-Amodi, Hussein; Gupta, Suruchi; Papatheodorou, Stefania I.; Hawkins, Robert; Ailawadi, Gorav; Mittleman, Murray A.; Chu, Michael W. A.
Objective: The safety of minimally invasive mitral valve surgery (MIMVS) in elderly patients is still debated. Our objective was to perform a systematic review and meta-analysis of studies comparing MIMVS with conventional sternotomy (CS) in elderly patients (≥65 years old). Methods: We searched PubMed, EMBASE, Web of Science, clinicaltrials.gov, and Cochrane Central Register of Controlled Trials for trials and observational studies comparing MIMVS with CS in patients ≥65 years old presenting for mitral valve surgery. We performed a random-effects meta-analysis of all outcomes. Results: The MIMVS group had lower odds of acute renal failure (odds ratio [OR] 0.27; 95% CI 0.10 to 0.78), prolonged intubation (>48 h; OR 0.47; 95% CI 0.31 to 0.70), less blood product transfusion (weighted mean difference [WMD] −0.82 units; 95% CI −1.29 to −0.34 units), shorter ICU length of stay (LOS; WMD −2.57 days; 95% CI −3.24 to −1.90 days) and hospital LOS (WMD −4.06 days; 95% CI −5.19 to −2.94 days). There were no significant differences in the odds of mortality, stroke, respiratory infection, reoperation for bleeding, and postoperative atrial fibrillation. MIMVS was associated with longer cross-clamp (WMD 11.8 min; 95% CI 3.5 to 20.1 min) and cardiopulmonary bypass times (WMD 23.0 min; 95% CI 10.4 to 35.6 min). Conclusions: MIMVS in elderly patients is associated with lower postoperative complications, blood transfusion, shorter ICU, and hospital LOS, and longer cross-clamp and bypass times.